Navigation Patterns from and to Social Media - Gamon, Michael; König, Arnd Christian (3rd AAAI Conference on Weblogs and Social Media (ICWSM 2009), 2009)
With the rapid rise of social media content, the question how people navigate to and from social media becomes important in order to understand what new tools and approaches are most beneficial to allow users to discover and interact with this social media data. In this study we analyze session log data to describe navigation patterns involving these sites. Our findings suggest that there are distinct patterns of insular navigation behavior around social media, with blogs being the most transitory in the way users interact with them.